Role of Ultrasound as Compared with ERCP in Patient With Obstructive Jaundice - Karki, S; Joshi, KS; Regmi, S; Gurung, RB; Malla, B (Kathmandu University Medical Journal, 2015)
Background The diagnosis of obstructive jaundice relies on proper history taking, clinical examination, laboratory investigations and different non invasive imaging modalities like Ultrasonography (USG), Cholangio Computed Tomography (CCT), Magnetic resonance Imaging (MRI) with Magnetic Resonance Cholangio Pancreatography (MRCP) and invasive modalities like endoscopic retrograde cholangiography (ERCP) and percutaneous trans hepatic cholangiography (PTC). Objective To compare the role of ultrasound with endoscopic retrograde cholangiography and to determine the major causes of obstructive jaundice in our prospect. Methods This was a prospective, analytical study conducted on 88 patients presenting to Department of Radiodiagnosis and Imaging at Dhulikhel Hospital-Kathmandu University hospital from March 2011 to August 2012 with clinical diagnosis of obstructive jaundice. Sonographic evaluation was performed in Siemens acusion x-150 and x-300. The final diagnosis was made by endoscopic retrograde cholangiography and /or surgery and confirmed histopathologically. Results The most common benign causes of obstructive jaundice were choledocholithiasis (63%), CBD stricture (12.3%), cholangitis (8%) and pancreatitis (6.85%) whereas cholangio carcinoma (6.85%) and carcinoma head of pancreas (4%) comprised of the malignant causes . Ultrasonography had sensitivity of 100% and specificity of 89% in detecting choledocholithiasis. It was found to be 98.78% sensitive and 83.33% specific in cholangiocarcinoma. Similarly in pancreatitis, the sensitivity of ultrasonography was 97.59% and sensitivity was 66.67%. Conclusion Ultrasonography acts as a valuable diagnostic imaging modality in detecting the causes of obstructive jaundice. Due to its easy availability, non invasive nature and cost effectiveness, it can be considered as the first line imaging technique/ tool. ERCP is the invasive imaging tool and can be used for both diagnostic and therapeutic purpose. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12512 Kathmandu Univ Med J 2013; 43(3):237-240